2018
DOI: 10.1007/s00339-018-1822-z
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser-induced herringbone patterns

Abstract: Femtosecond laser-induced herringbone patterns are formed on copper (Cu). These novel periodic structures are created following s-polarized, large incident angle, femtosecond laser pulses. Forming as slanted and axially symmetric laser-induced periodic surface structures along the side walls of ablated channels, the result is a series of v-shaped structures that resemble a herringbone pattern. Fluence mapping, incident angle studies, as well as polarization studies have been conducted and provide a clear under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Figure 1g demonstrates the possibility of producing microgrooves decorated with both tilted and horizontal LSFLs/HSFLs (magnified images are also shown in Figure 1h,i). The orientation of LSFLs/HSFLs pointed out by a green arrow is perpendicular to the direction of light polarization (Figure 1h), while the tilted LSFLs/HSFLs deviate by 18 • from the microgroove direction, as expected (Figure 1i), resembling the herringbone structures on copper surfaces obtained by s-polarized fs laser ablation at a large incident angle [45]. Schwarz et al reported that an inclined fs laser can significantly alter the orientations of LSFLs on fused silica [46].…”
Section: Methodssupporting
confidence: 70%
“…Figure 1g demonstrates the possibility of producing microgrooves decorated with both tilted and horizontal LSFLs/HSFLs (magnified images are also shown in Figure 1h,i). The orientation of LSFLs/HSFLs pointed out by a green arrow is perpendicular to the direction of light polarization (Figure 1h), while the tilted LSFLs/HSFLs deviate by 18 • from the microgroove direction, as expected (Figure 1i), resembling the herringbone structures on copper surfaces obtained by s-polarized fs laser ablation at a large incident angle [45]. Schwarz et al reported that an inclined fs laser can significantly alter the orientations of LSFLs on fused silica [46].…”
Section: Methodssupporting
confidence: 70%
“…Thus, P_a structures can be characterized as heterostructure between nanostructures and microstructures. P_b laser treatment results in the formation of "herringbone" structures (Figure 2b,d,f), which were firstly demonstrated in the work of Garcell et al [24]. The herringbone structures constitute a singular channel with angled and axially symmetric ripples.…”
Section: Resultsmentioning
confidence: 72%
“…In the past, most papers focused on generating LIPSS on plant surfaces by different scanning strategies or polarization [ 6 , 7 , 8 , 9 ]. Recent studies recently investigated LIPSS by the p-polarized laser beam with oblique incidence on the sample surface [ 10 , 11 , 12 , 13 ]. These studies found that the polarization portion irradiated on the hole and groove sidewall changes with the incidence angle.…”
Section: Introductionmentioning
confidence: 99%